Thyroidectomy with Tracheal/Cricotracheal Resection Anastomosis for Different Pathologies: Optimizing the Outcomes - Abd-Elfattah, Ahmed Musaad; Tawfik, Ali; Hossam, Amr; Mohammed, Mohammed Nashaat; Ebada, Hisham Atef (International Archives of Otorhinolaryngology, 2025)
Thyroid cancer extending to trachea has a poor prognosis. Deep tracheal invasion necessitates circumferential tracheal resection and anastomosis with thyroidectomy to achieve radical resection. Thyroid gland invasion by advanced tracheal tumors is rare. Similarly, tracheal resection with thyroidectomy is the treatment of choice for these cancers.Neck trauma that results in simultaneous damage of a tracheal segment and thyroid gland, may necessitate tracheal resection with thyroidectomy.The aim of this study was to evaluate the oncologic and functional outcomes in patients who had undergone thyroidectomy with tracheal/cricotracheal resection anastomosis for pathologies involving both a thyroid gland and airway.This is a study that was conducted over 5 years on 11 patients who underwent thyroidectomy with tracheal/cricotracheal resection for pathologies involving both the thyroid gland and the airway (thyroid gland tumors, primary tracheal tumors, and traumatic impaction of the thyroid gland in the trachea).Successful outcomes were achieved in all patients. No intraoperative complications were reported. Minor postoperative complications were reported in 1 patient, in the form of limited surgical emphysema and air leak through the drains.Tracheal/cricotracheal resection anastomosis represents the best compromise between oncologic radicality and postoperative quality of life. Highly skilled teams familiar with these types of airway surgery are required to achieve optimum results.
Keywords: thyroidectomy; tracheal stenosis; tracheal neoplasms; thyroid neoplasms; anastomosis